LANGUAGE AS A CATALYST: SHAPING THE EVOLUTION OF EDUCATION - Akhmadova Maftuna Ibodullo qizi; Muxiddinova Fariza Nuriddinovna (Research Focus International Scientific Journal, 2025)
Language is the foundation of education and serves as the primary medium of instruction. A well-structured education system must consider linguistic diversity to ensure effective learning- Research suggests that students who receive instruction in their mother tongue have better academic outcomes. This paper explores the role of language in education, the benefits and challenges of multilingual education, and the impact Of language policies on learning